Milton Cross' complete stories of the great operas - Cross, Milton (Milton John) 1897-1975 (Garden City, New York Doubleday & Company, Inc., 1952)
Descriptions of famous operas, including plot, dialogue, and important arias.
pt. I, The stories of the great operas : -- L'Africaine / Meyerbeer -- Aida / Verdi -- L'Amore Dei Tre Re / Montemezzi -- Andrea Chenier / Giordano -- Ariadne auf Naxos / Strauss -- Un Ballo in Maschera / Verdi -- Il Barbiere di Siviglia / Rossini -- The bartered bride / Smetana -- La boheme / Puccini -- Boris Godunof / Moussorgsky -- Carmen / Bizet -- Cavalleria rusticana / Mascagni -- Les Contes d'Hoffmann / Offenbach -- Le Coq d'Or / Rimsky-Korsakov -- Cosi Fan Tutte / Mozart -- Don Giovanni / Mozart -- Don Pasquale / Donizetti -- Elektra / Strauss --L'Elisir d'Amore / Donizetti -- Die Entfuhrung aus dem Serail / Mozart -- Eugen Onegin / Tschaikowsky -- Falstaff / Verdi -- Faust / Gounod -- Fedelio / Beethoven -- La Figlia del Reggimento / Donizetti -- Der Fliegende Hollander / Wagner -- La Forza del Destino / Verdi -- Der Freischutz / Weber -- Gianni Schicchi / Puccini -- La Gioconda / Ponchielli -- Hansel und Gretel / Humperdinck -- Les Huguenots / Meyerbeer -- La Juive / Halevy -- Lakme / Delibes -- Lohengrin / Wagner -- Louise / Charpentier -- Lucia di Lammermoor / Donizetti -- Madama Butterfly / Puccini -- Manon / Massenet -- Manon Lescaut / Puccini -- Martha / Flotow -- Mefistofele / Boito -- Die Meistersinger von Nurnberg / Wagner -- Mignon / Thomas -- Norma / Bellini -- Le Nozze di Figaro / Mozart -- Orfeo ed Euridice / Gluck -- Orfeo ed Euridice / Gluck --Otello / Verdi -- Pagliacci / Leoncavallo -- Parsifal / Wagner -- Les Oecheurs de Perles /Bizet -- Pelleas et Melisande / Debussy -- Pique-Dame / Tschaikowsky -- Rigoletto / Verdi -- Der Ring des Nibelungen / Wagner -- Romeo et Juliette / Gounod -- Der Rosenkavalier / Strauss -- Salome / Strauss -- Samson et Dalila / Saint-Saens -- Simon Boccanegra / Verdi -- La Sonnambula / Bellini -- Tannhauser / Wagner -- Thais / Massenet -- Tosca / Puccini -- La Traviata / Verdi -- Tristan und Isolde / Wagner -- Il Trovatore / Verdi -- Turandot / Puccini -- Die Zayberflote / Mozart -- pt. II, How to enjoy the opera -- pt. III, A brief history of opera -- pt. IV, The ballet in opera.
Includes bibliographical references (pages [615]-616) and index.
Keywords: Operas -- Stories, plots, etc